2020
DOI: 10.1109/jlt.2020.2994300
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Effects of Dislocations in Monolithic III-V Lasers on Silicon

Abstract: In this work, we present an approach to modelling III-V lasers on silicon based on a travelling-wave rate equation model with sub-micrometer resolution. By allowing spatially resolved inclusion of individual dislocations along the laser cavity, our simulation results offer new insights into the physical mechanisms behind the characteristics of 980 nm In(Ga)As/GaAs quantum well (QW) and 1.3 m quantum dot (QD) lasers grown on silicon. By studying the reduction of the local gain in carrierdepleted regions around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Dislocations arise from strain relaxation when growing a layer with a lattice constant different than that of the substrate, and are thus unavoidable. Since they act as non-radiative recombination centers, the density of threading dislocations should in principle be reduced to limit device degradation 51 , 52 . When GaSb is grown on substrates such as GaAs or Si, the large lattice-mismatch (8 or 12%, respectively) induces the formation of an interfacial network of edge-type misfit dislocations 53 57 that provides the most efficient strain-relaxation pathway 58 .…”
Section: Epitaxial Growth Of Antimonide Heterostructures On (001)si S...mentioning
confidence: 99%
“…Dislocations arise from strain relaxation when growing a layer with a lattice constant different than that of the substrate, and are thus unavoidable. Since they act as non-radiative recombination centers, the density of threading dislocations should in principle be reduced to limit device degradation 51 , 52 . When GaSb is grown on substrates such as GaAs or Si, the large lattice-mismatch (8 or 12%, respectively) induces the formation of an interfacial network of edge-type misfit dislocations 53 57 that provides the most efficient strain-relaxation pathway 58 .…”
Section: Epitaxial Growth Of Antimonide Heterostructures On (001)si S...mentioning
confidence: 99%
“…In contrast, there was no lasing observed for the QW device at roomtemperature even at higher injection levels. After comparing with modelling results, this study indicated that QW laser cannot work properly above 10 7 cm À2 of TDD [100,101]. Figure 28c presented a temperature dependent light-current curve of QD laser on Si (001).…”
Section: Inas/gaas Qd Laser On On-axis Si (001) Substratementioning
confidence: 87%
“…As discussed in the first section of this chapter, the heteroepitaxy technique on on-axis Si (001) was satisfied by forming APB-free GaAs buffer. Beyond the successful demonstration of QD lasers on offcut Si platform, QD lasers grown on CMOS-compatible Si (001) substrate were successfully developed in recent years [98][99][100][101][102][103][104][105], owing to the demonstration of the APB-free GaAs and GaP templates on Si.…”
Section: Inas/gaas Qd Laser On On-axis Si (001) Substratementioning
confidence: 99%
“…Si/SiO2 waveguides. Additionally, dislocations can be present even in the QD-layer region leading to non-radiative recombination of minority carriers and gain compression effects as observed in directly modulated Si-based QD lasers [86].…”
Section: Group-iii-v On Group-iv Approachesmentioning
confidence: 99%